Terror/Emergency Preparedness - Mary Harrison; Lisa Guion (EDIS)
Terror is the most effective when it creates a sense of uncertainty, confusion and traumatic, paralyzing fear. Your best defense against terror is the ability to keep calm and to make rational decisions. Be alert. Be suspicious of abnormal or unusual situations. But, do not spend time and energy worrying about the situation. There are unexpected events that occur. Terror preparations are similar to preparations for other emergencies and disasters.